Clinical and radiographic response of a paravertebral hemangioma to radiotherapy - Laura Burgess, MSc, MD; Julia Malone, BSc; Marlise P. dos Santos, MSc,MPH, MD; John Sinclair, MD; Osbert Zalay, MD, PhD; Shawn Malone, MD (Radiology Case Reports, 2024)
Hemangiomas can arise anywhere in the body. While vertebral hemangiomas are common, atypical hemangiomas with paraspinal and epidural extension are rare. We present a case of a patient who presented with persistent cough and anorexia from a paravertebral hemangioma that invaded the adjacent vertebrae and neural foramen causing moderate spinal canal stenosis. She was treated with stereotactic body radiotherapy to prevent the development of symptomatic spinal cord compression. The hemangioma underwent significant shrinkage and her cough resolved. This case demonstrates impressive and sustained clinical and radiographic response of a paraspinal hemangioma to stereotactic body radiotherapy.